Sovereign Bond Restructuring : Collective Action Clauses and official Crisis Intervention - Kletzer, Kenneth (IMF Working Papers; Working Paper ;, 2003)
This paper compares the restructuring of sovereign bonds with and without collective action clauses. One conclusion is that collective action clauses can allow efficient debt renegotiation in a formal model of sovereign debt renegotiation while unanimity rules offer incentives for opportunistic behavior by bondholders that leads to inefficient outcomes. With collective action clauses, the mutual gains from renegotiation can be internalized by bondholders so that the holders of each bond issue have incentives to participate in a collective debt restructuring. The analysis abstracts from transactions costs, and the last conclusion might well be sensitive to renegotiation and coordination costs.